A Perspective of Evolution for Carbon Emissions Trading Market: The Dilemma between Market Scale and Government Regulation - Qi Zhu (Discrete Dynamics in Nature and Society)
Which means are more effective for reducing carbon emission? Our paper argues the effect of the government regulation and the market trading on the carbon emission. Based on our model, we obtain three conclusions as follows. First, government strengthened regulation can encourage firms to participate in the trading market for carbon emission. Second, there is the negative relation of supervision cost to trading price. Third, there is an alternative relationship between the scale economy level of the supervisory authority and that of the carbon emissions market. Meanwhile, our numerical simulations also confirm our results for our model analyses.